Association of dietary decanoic acid intake with diabetes or prediabetes: an analysis from NHANES 2005–2016 - Zhu, Huangxin; Fu, Qingan; Chen, Ruxin; Luo, Linfei; Yu, Miao; Zhou, Yue (Frontiers in Nutrition, 2025)
BackgroundWith the increasing prevalence of prediabetes and diabetes, exploring dietary factors associated with prediabetes and diabetes has become a global health research priority. This study aimed to assess the relationship between dietary decanoic acid (DDA) intake and the risk of diabetes and prediabetes.MethodsData from the National Health and Nutrition Examination Survey (NHANES) 2005–2016 included 11,477 adult participants. DDA intake was assessed through two 24-h dietary recalls and participants were grouped according to the diagnostic criteria for diabetes and prediabetes. Multivariate regression models were applied to analyze the relationship between DDA intake and diabetes and prediabetes, with subgroup analyses conducted to explore potential interactions.ResultsDietary decanoic acid intake was significantly negatively associated with the risk of diabetes. In the fully adjusted model, each 1 g/day increase in DDA intake was associated with a 19% reduction in the odds of developing diabetes from prediabetes (OR = 0.81, 95% CI: 0.68–0.96, p = 0.015) and this negative association was more pronounced in individuals with higher education level (P for interaction = 0.006). Compared with the DDA intake ≤0.18 g/day, DDA intake >0.58 g/day is related to reduced risk of progression to diabetes in prediabetic patients. However, the relationship between DDA intake and the risk of prediabetes was not statistically significant in the fully adjusted model (OR = 0.95, 95% CI: 0.84–1.07, p = 0.404).ConclusionThis study found that higher DDA intake may be associated with lower prevalence of diabetes among prediabetic population, and high education level strengthen this relationship.